Pemberdayaan Masyarakat Desa Watunohu Kabupaten Kolaka Utara dalam Pengolahan Biji Kakao menjadi Usaha Tepung Terstandar dan Tersertifikasi Halal: Empowering the Community of Watunohu Village, North Kolaka Regency in Processing Cocoa Beans into a Halal Certified and Standardized Flour Business - Saparuddin, Saparuddin; Alimuddin, Alimuddin; Tojang, Djunarlin; Arham, Zul; Ismaun, Ismaun; Irwan, Irwan; MgB, A. Fadilah; Nurhijayanti, Nurhijayanti; Akila, Nur (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Watunohu Village is one of the villages in North Kolaka Regency, Southeast Sulawesi, which has great potential in cocoa production. However, the utilization of cocoa beans, especially by the PKK group, is still limited to the traditional post-harvest stage without further processing. This activity aims to improve the skills and knowledge of PKK mothers in processing cocoa beans into cocoa flour that meets national standards (SNI) and is halal certified. This training is also expected to open up new business opportunities and improve community welfare. The training method used is the socialization method and direct demonstration with mentoring of joint practice with the community. The activity results showed a significant increase in participants' understanding of the cocoa bean processing process, as well as high enthusiasm for developing cocoa derivative products. Participants were able to produce cocoa flour that meets quality standards and has the potential to be developed as a superior village product. In addition, participants also gained an understanding of the importance of a production process that is by Islamic law so that the resulting product can be halal-certified. The training activity ended with the handover of cocoa flour-making technology to the Head of Watunohu Village.